THE FUTURE OF RESTAURANT BUSINESS IN UKRAINE: TRENDS AND MARKET DEVELOPMENT OPPORTUNITIES (Development Service Industry Management, 2023)
The article identifies the challenges faced by the Ukrainian restaurant industry amidst the difficult economic crises, the COVID-19 pandemic, and the ongoing conflict. Market dynamics, consumer preferences, and market trends are analyzed, emphasizing the resilience and adaptability demonstrated by restaurateurs. The author underlines the growing need for adaptive strategies to overcome unprecedented challenges, providing insights into market shifts, changing consumer behavior, and strategies used by businesses to survive and grow. In addition, the article examines the impact of the war on the industry, focusing on the analysis of statistics on the closure and opening of new establishments, and exploring the geographical differences in the restaurant market. The article highlights the role of restaurant business enterprises in supporting society, their resilience and efforts to continue operations despite the adversity. The research aims to guide restaurateurs by offering vital recommendations and insights for the industry's revival and long-term sustainability.
Keywords: restaurant business; restaurant establishment; trends; market; development; consumer demand